SINERGI MAHASISWA KKL DAN KOMUNITAS DESA SILAIYA DALAM MENINGKATKAN LITERASI AL-QUR'AN ANAK-ANAK - Yulia Ningsih; Rahmayana Siregar; Lia Rizky Wulandari Harahap; Emmi Sapia Hasibuan (Yayasan Baitul Hikmah al-Zain, 2026)
Fieldwork (KKL) activities play a crucial role in developing Quranic literacy skills in the community. This study aims to describe the contribution of KKL students in improving Quranic literacy skills of children in Silaiya Village. Through mentoring, direct instruction, and the use of simple learning media, the students successfully created an effective and enjoyable learning environment. The results of the activities showed an increase in the ability to recognize the hijaiyah letters, read the Iqra', and strengthen the children's learning motivation. This program demonstrates that the involvement of KKL students can have a positive impact on religious education in the village.